Neospora caninum infection in birds: experimental infections in chicken and embryonated eggs - Furuta, P. I. [UNESP]; Mineo, T. W. P. [UNESP]; Carrasco, A. O. T. [UNESP]; Godoy, G. S. [UNESP]; Pinto, A. A. [UNESP]; Machado, R. Z. [UNESP] (Cambridge University Press, 2007)
Neospora caninum causes economical impact in cattle-raising farms since it is implicated as the major cause of bovine abortions. Although infection by the parasite has been widely described in mammals, the role of birds in its life-cycle is still obscure. Therefore, this work aimed to evaluate the infection by N. caninum in different chicken models. Experimental infections were conducted in 7-day-old chicks, laying hens and embryonated eggs, where samples were analysed for parasite burden, IgG antibodies and lesions promoted. Chickens demonstrated an asymptomatic infection, although with seroconversion and systemic replication of the parasite. In laying hens, no signs of vertical transmission were observed. However, embryonated eggs inoculated by the allantoic cavity route demonstrated susceptibility to infection, with mortality rates around 50% independent of the inoculum dose. Additionally, dogs became infected after ingestion of different amounts of inoculated eggs, producing either oocysts or specific IgG antibodies. The results herein presented demonstrate that chickens may be intermediate hosts of N. caninum and that embryonated eggs could be a useful model to study the parasite's biology.
Keywords: Neospora caninum; chicken; embryonated eggs; laying hens; dogs; experimental infections